BUCURIA SERENDIPITĂŢII ADUCE IDEI - HARJEVSCHI, Mariana (BIBLIOPOLIS, 2020)
Serendipity as a “fortunate happenstance” or “pleasant surprise” can play an important role in the search for truth, but is often ignored in the scientific literature because of traditional scientific behavior and scientific thinking based on logic and predictability. Author underlines that serendipitous events occurred in libraries can generate important ideas for various projects, activities in library. It is recognized and appreciated the unexpected situations, can tend to encourage librarians to observe and discuss unexpected events leading to new good ideas.